"If not, why not" form of governance: Do firm-specific variables explain the nature of justification?. Issue 2 (1st July 2019) - Lama, Tek; Anderson, Warwick Wyndham
Abstract : Purpose: Are the explanations that companies provide when deviating from two board structure-related best practices under the Australian Stock Exchange's "If not, why not" regulatory regime systematically influenced by company characteristics? Design/methodology/approach: Multinomial logistic regressions are performed on a sample of 258 ASX-listed firms in the period 2004-2007. The dependent variable is the level of response to the "why not" pillar of the regime which requires companies to provide an explanation where they deviate from the recommended governance practice or practices. The variable is categorised into three levels: zero response, inadequate explanation and adequate explanation. This variable takes on a fourth possible level (full compliance) if both pillars of the regime are considered jointly. The independent variables are company size, ownership concentration, profitability, liquidity, age and the market-to-book ratio. Findings: The regime appears to be well specified, but size is positively correlated to the quality of explanations given for the deviation. Other company characteristics have no important systematic effect. Practical implications: Small firms, while availing of the regulatory flexibility that enables them to adopt governance systems that suit their corporate governance requirements, tend not to meet the reporting requirements that go with that flexibility. Originality/value: To the best of the authors' knowledge, this paper is one of the first to explore the justifications given for deviations from full compliance in the "if not why not" regime and covers new ground with respect to explanations given for non-adoption of board structure recommendations.